Meningkatkan Karakter Peserta Didik di Era Digital Melalui Kegiatan Pembinaan Pendidikan Karakter Religius - Yakobus Belo Tobi; Yasinta Uto Doren; Servina Retno Anna Lewar; Yustina P. Prada Tolok; Waltrudis Safira Naibae; Rina Ola Ina; Yosep Belen Keban (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2025)
Community Service activities by the Yehezkiel group targeting Catholic students at SDI Lamanabi through religious character development activities need to be conducted in this digital era.This is important because students are trapped in the digital era and live far from religious activities, such as being less involved in spiritual activities, having an indifferent attitude, being lazy in studying, lacking discipline, not participating in prayers and youth activities, and showing a lack of politeness in social interactions. This activity aims to enhance the character of students at SDI Lamanabi, Paroki Waiklibang in the digital era through religious character education development activities. The method used in this community service activity is a training method through the provision of materials, question and answer sessions, and participation. This activity was conducted on November 15-17, 2024. The result of this activity is the awareness among the students at SDI Lamanabi-Tanjung Bunga to embody religious values or character in their lives amidst the advancement of digital technology. The result of this service certainly makes the students at SDI Lamanabi engage in religious activities to enhance their religious character in the digital era.